Associations of acoustically measured tongue/jaw movements and portion of time speaking with negative symptom severity in patients with schizophrenia in Italy and the United States. (30th May 2016) - Bernardini, Francesco; Lunden, Anya; Covington, Michael; Broussard, Beth; Halpern, Brooke; Alolayan, Yazeed; Crisafio, Anthony; Pauselli, Luca; Balducci, Pierfrancesco M.; Capulong, Leslie; Attademo, Luigi; Lucarini, Emanuela; et al.
Abstract: This is the first cross-language study of the effect of schizophrenia on speech as measured by analyzing phonetic parameters with sound spectrography. We hypothesized that reduced variability in pitch and formants would be correlated with negative symptom severity in two samples of patients with schizophrenia, one from Italy, and one from the United States. Audio recordings of spontaneous speech were available from 40 patients. From each speech sample, a file of F0 (pitch) and formant values (F1 and F2, resonance bands indicating the moment-by-moment shape of the oral cavity), and the portion of the recording in which there was speaking ("fraction voiced, " FV), was created. Correlations between variability in the phonetic indices and negative symptom severity were tested and further examined using regression analyses. Meaningful negative correlations between Scale for the Assessment of Negative Symptoms (SANS) total score and standard deviation (SD) of F2, as well as variability in pitch (SD F0) were observed in the Italian sample. We also found meaningful associations of SANS affective flattening and SANS alogia with SD F0, and of SANS avolition/apathy and SD F2 in the Italian sample. In both samples, FV was meaningfully correlated with SANS total score, avolition/apathy, and anhedonia/asociality. Highlights: We analyzed the effect of Schizophrenia on speech using sound spectrography. Our analysis was conducted in two cross-languages samples. Computationally derived phonetic indices are of potential utility in measuring and tracking negative symptoms.